Eco-Cultural Tourism through Community Participation: Promoting Environmentally Friendly Practices and Cultural Preservation in Prachinburi Province - Siramaneerat, Issara; Thanapotivirat, Pornnapa; Aree, Usana; Hussadin, Areewan (Research in Ecology, 2025)
This study investigates the role of community participation in promoting eco-cultural tourism with a focus on environmentally friendly practices and cultural preservation in Si Maha Phot District, Prachinburi Province, Thailand. Conducted as a cross-sectional survey, the research sampled 400 individuals from a population of 85,988, using Taro Yamane’s formula for sample selection. Data collection took place from March 1 to 31, 2024, gathering information on individual demographics, levels of community engagement, eco-cultural tourism knowledge, and perceptions of tourism impacts. Statistical analyses, including frequency, percentage, mean, standard deviation and multi-classification analysis (MCA), explored the relationship between socio-demographic factors and community participation in eco-cultural tourism. The analysis revealed significant overall differences, with an F-value of 14.662 and p = 0.000, indicating that the analyzed factors substantially impact eco-friendly tourism development. Age was found to have a highly significant effect (F = 37.602, p = 0.000), showing a strong relationship between respondents’ age and environmentally friendly tourism development. Additionally, eco-tourism knowledge was significantly influential (F = 7.658, p = 0.006), highlighting the role of awareness in shaping community behavior. Moreover, tourism-derived income significantly influenced eco-friendly tourism development (F = 52.137, p = 0.000), underscoring the economic benefits from tourism in fostering community engagement. Furthermore, significant differences were observed for gender, marital status, education, and community residence, showing statistical significance (p < 0.05). Findings underscore the potential of educational and cultural awareness initiatives to enhance community engagement in eco-cultural tourism, suggesting targeted educational efforts as a means for policymakers and stakeholders to foster sustainable tourism practices that respect both the environment and cultural heritage.